Exploring NamiRNA networks and time-series gene expression in osteogenic differentiation of adipose-derived stem cells - Xin Jin; Yi Lu; Zhihong Fan (Annals of Medicine)
Background Adipose-derived stem cells (ADSCs) are a type of stem cell found in adipose tissue with the capacity to differentiate into multiple lineages, including osteoblasts. The differentiation of ADSCs into osteoblasts underlies osteogenic and pathological cellular basis in osteoporosis, bone damage and repair.Methods Focused on ADSCs osteogenic differentiation, we conducted mRNA, microRNA expression and bioinformatics analysis, including gene differential expression, time series-based trend analysis, functional enrichment, and generates potential nuclear activating miRNAs (NamiRNA) regulatory network. The screened mRNAs in NamiRNA regulatory network were validated with correlation analysis.Results The NamiRNA Regulatory Network reveals 4 mRNAs (C12orf61, MIR31HG, NFE2L1, and PCYOX1L) significantly downregulated in differentiated group and may be associated with ADSCs stemness. Furthermore, the significantly upregulated 10 genes (ACTA2, TAGLN, LY6E, IFITM3, NGFRAP1, TCEAL4, ATP5C1, CAV1, RPSA, and KDELR3) were significantly enriched in osteogenic-related pathways, and negatively correlated with ADSCs cell stemness in vitro.Conclusion These findings uncover potential genes related to ADSCs osteogenic differentiation, and provide theoretical basis for underlying ADSCs osteogenic differentiation and related diseases.